(untitled) (Orinoquia, 2020)
Cryopreservation is a biotechnological tool that in fish is mainly aimed at cryogenic conservation of semen as a strategy for preserving the genetic resource and its use for the production of fingerlings with different purposes. Currently, seminal cryopreservation protocols in freshwater fish establish a wide variety of procedures whose effectiveness is based on aspects linked to seminal post-thaw quality and fertility, as well as its relationship with the development of the progeny. The effectof preserving semen in liquid nitrogen for extended periods of time also plays an important role in this biotechnology. Therefore, the objective of this review is to describe biotechnological, cellular and biochemical aspects associated with the seminal cryopreservation process in freshwater fish, highlighting the advances, limitations and perspectives.